Financial Ratio Analysis in Assessing Financial Performance at PT. Mustika Ratu, Tbk. Listed on the Indonesia Stock Exchange in 2019-2023 - Aswindah Dakhi; Laily Ramadhani; Rifqah Harahap (Global Insights in Management and Economic Research, 2025)
Purpose of the study: This study aims to evaluate the financial performance of PT Unilever Indonesia Tbk during the 2019–2023 period using profitability ratios, namely Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE), benchmarked against industry standards. Materials and methods: This research employed a qualitative descriptive approach using secondary data derived from the audited annual financial statements of PT Unilever Indonesia Tbk for the period 2019–2023. Data were collected through documentation techniques and analyzed using profitability ratio analysis. Industry benchmark standards were used as comparative references to assess company performance. Results: The findings indicate that the average Net Profit Margin (14%) remained below the industry standard (20%), reflecting suboptimal profitability. The average Return on Assets (31%) met the industry benchmark (30%), indicating effective asset utilization. Conversely, the average Return on Equity (138%) substantially exceeded the industry standard (40%), suggesting inefficiencies in equity structure and capital utilization. Conclusions: Overall, PT Unilever Indonesia Tbk demonstrated mixed financial performance during 2019–2023. Asset utilization was efficient, while profitability from sales and equity management showed structural weaknesses. These findings provide important insights for managerial decision-making and future financial strategy formulation.